2020
DOI: 10.1039/d0ra05786j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticles-anchored dual-responsive SBA-15-PNIPAM/PMAA nanoreactor: a novel heterogeneous catalyst for a green Suzuki–Miyaura cross-coupling reaction

Abstract: Palladium nanoparticles-anchored dual-responsive SBA-15-copolymer nanoreactor was developed as a novel heterogeneous catalyst for green Suzuki–Miyaura cross-coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Ha et al synthesized dual (temperature and pH)-responsive poly(N-isopropyl acrylamide-co-methacrylic acid) functionalized SBA-15. This material supported the fact that Pd NPs showed high catalytic activity for Suzuki-Miyaura coupling reactions at room temperature, while the activity decreased at higher temperature than LCST of PNIPAM [190]. It has been reported that Suzuki-Miyaura coupling reaction proceeded at room temperature using Pd NPs stabilized on CaAl-layered double hydroxide functionalized with tris(hydroxymethyl)aminomethane (Scheme 18) [191].…”
Section: Organic-inorganic Compositessupporting
confidence: 63%
“…Ha et al synthesized dual (temperature and pH)-responsive poly(N-isopropyl acrylamide-co-methacrylic acid) functionalized SBA-15. This material supported the fact that Pd NPs showed high catalytic activity for Suzuki-Miyaura coupling reactions at room temperature, while the activity decreased at higher temperature than LCST of PNIPAM [190]. It has been reported that Suzuki-Miyaura coupling reaction proceeded at room temperature using Pd NPs stabilized on CaAl-layered double hydroxide functionalized with tris(hydroxymethyl)aminomethane (Scheme 18) [191].…”
Section: Organic-inorganic Compositessupporting
confidence: 63%
“…The results also exhibited the deconvolution of C 1s into three peaks: (1) a peak pertaining to the C–N and C–S bonds at 286.29 eV, (2) a peak related to the C–C or C–H bonds at 284.60 eV, and (3) a peak associated with the H 2 N–CO bond in the AMPS and MBA at 288.46 eV. 55,56 Illustrating the N 1s spectra of the p(NIPAM- co -AMPS)-Ag-L nanocomposite, Fig. 3 displays a peak generated by the interaction of C–N, CO–NH 2 in NIPAM and Ag nanoparticles at 398.30 eV.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 2 shows XP spectra of the mesoporous silica. Survey region ( Figure 2 a) clearly shows a quasi-neat silica, similar to calcined mesoporous silica [ 30 ]. Interestingly, CTAB has been removed after synthesis as the Br3d and N1s regions are flat and noisy ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 98%